Variation in HNF1B and Obesity May Influence Prostate Cancer Risk in African American Men: A Pilot Study - Ganna Chornokur; Ernest K. Amankwah; Stacy N. Davis; Catherine M. Phelan; Jong Y. Park; Julio Pow-Sang; Nagi B. Kumar (Prostate Cancer)
Background. Prostate cancer (PCa) racial disparity is multifactorial, involving biological, sociocultural, and lifestyle determinants. We investigated the association between selected potentially functional polymorphisms (SNPs) and prostate cancer (PCa) risk in Black (AAM) and White (EAM) men. We further explored if these associations varied by the body mass index (BMI) and height. Methods. Age-matched DNA samples from 259 AAM and 269 EAM were genotyped for 10 candidate SNPs in 7 genes using the TaqMan allelic differentiation analysis. The dominant, recessive, and additive age-adjusted unconditional logistic regression models were fitted. Results. Three SNPs showed statistically significant associations with PCa risk: in AAM, HNF1B rs7501939 (OR=2.42, P=0.0046) and rs4430796 (OR=0.57, P=0.0383); in EAM, CTBP2 rs4962416 (OR=1.52, P=0.0384). In addition, high BMI in AAM (OR=1.06, P=0.022) and height in EAM (OR=0.92, P=0.0434) showed significant associations. Interestingly, HNF1B rs7501939 was associated with PCa exclusively in obese AAM (OR=2.14, P=0.0103). Conclusion. Our results suggest that variation in the HNF1B may influence PCa risk in obese AAM.